VALORILE UNIVERSALE ÎN CONTEXTUL DUBLULUI REGIM TOTALITAR DIN REPUBLICA SOVIETICĂ BELARUS, REFLECTATE ÎN OBELISCUL DE V. BÂKOV (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2025)
Universal Values in the Double Totalitarian Regime of the Soviet Belarusian Republic, Reflected in The Obelisk by V. Bykov.The article reveals the dilemmatic heroism of a Belarusian teacher under the Nazi occupation, posing the core questions of the Soviet war prose regarding the heroic deed (podvig) in war, heroism and heroization. Deeply concerned with universal values, teacher Ales Moroz from Bykov’s story The Obelisk disregarded the Soviet curriculum and focused on imbuing his pupils with different principles and moral standards. Moreover, his dedication to his pupils extended during the Nazi occupation when he decided to reopen the school and, in an unfortunate series of events, chose to die alongside his pupils, nevertheless saving one of them.